The role of proximity to universities for corporate patenting: Provincial evidence from China - Wan-Hsin Liu (Kiel Institute for the World Economy (IfW), 2012)
This paper investigates whether proximity to universities matters for corporate patenting in Chinese provinces. The investigation is based on estimating regional knowledge production functions using a Chinese provincial dataset for the years from 2000 to 2008. Geographic proximity of companies to universities is taken as a key element to measure firms' accessibility to university research. In addition, quality-adjusted accessibility measures are considered in extended models to take into account quality difference in university research. The results suggest the existence of spatial academic effects on corporate patenting activities in China as found in the previous literature for Western economies. In China, however, these effects are especially strong for realising technologically less demanding non-invention corporate patents than for invention corporate patents. Moreover, companies' geographic proximity to universities dominates over university research quality difference for determining the relevance of universities as knowledge sources for companies. Extended models are estimated for robustness checks which ascertain the main results.
Keywords: O31; O53; R11; 330; spatial proximity; logsum accessibility; university; corporate patenting; China